Mal(-)dito Brasil: o regional e o nacional nos escritos de Paulo Prado (1922-1934) - Muto, Sílvia (2008)
The following dissertation aims at reflecting on the relationship between history and the intellectual constitution of the emotional memory in the process of creating local and national identities. This study analyses the relation between Paulo Prado s books Paulística (1925) and Retrato do Brasil (1928) and the early 1900 s Society in Brazil, and in the city of São Paulo. Struggling to build a Brazilian identity, Paulo Prado s work sheds light into the links between Nation, modernism and local culture. Moreover, it investigates the importance of recorded history in building up local and national identities